Calculus

posted by .

use implicit differentiation to find dy/dx if x^3+y^3=6xy

  • Calculus -

    3x^2 + 3y^2 dy/dx = 6x dy/dx + 6y
    dy/dx(3y^2 - 6x) = 6y - 3x^2

    dy/dx = (6y - 3x^2)/(3y^2 - 6x)
    = (2y - x^2)/(y^2 - 2x)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math - Calculus Question.

    hey can someone explain to me the relationship between the chain rule and implicit differentiation?
  2. Calculus 1 - implicit differentiation

    I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
  3. Calculus 1 - implicit differentiation

    I do not understand implicit differentiation. One of the problems are: find y' by implicit differentiation xy+2x+3x^2=4. I would appreciate any help that can be offered.
  4. calculus; implicit differentiation

    Use implicit differentiation to find the slope of the tangent line to the curve at the point (4,1) -1x^2 - 4xy + 3y^3 = -29 I differentiated both sides and solved for dy/dx and got 2x-4y/9y^2-4x. Then I plugged in X and Y and got -4/7 …
  5. Implicit Differentiation

    Use implicit differentiation to find the slope of the tangent line to the curve y/x+6y=x^2–6 at the point (1,–5/31) . Again i think i'm messing up with the algebra here. I used quotient rule to get [(x+6y)(y')-(y)(1+6y')]/(x+6y)^2=2x …
  6. Calculus

    How do you use imlicit differentiation to differentiate e^(xy)?
  7. Implicit differentiation calculus

    PLEASE HELP , I DON'T UNDERSTAND find dy/dx by implicit differentiation a) xy + x^5y^2 + 3x^3 - 4 = 1 b) lny = cos x thank you
  8. Calculus

    use implicit differentiation to find dy/dx if x^3+y^3=6xy
  9. Calculus [Implicit Differentiation]

    If √x+√y=10 and y(16)=36, find y'(16) by implicit differentiation. If somebody could please help me by explaining how to solve this problem ! Thank you (:
  10. Calculus: implicit differentiation

    Find dy/dx by implicit differentiation 1. x^3 -xy+ y^2= 7 The given answer is (y-3x^2)/ (2y-x), but I'm not getting it. 2. How would I do this one?

More Similar Questions